A tipping point for agricultural expansion? Technological changes and capital accumulation in Argentina's rural sector. (13th August 2019) - Cáceres, Daniel M.; Gras, Carla
Abstract: Drawing upon a case study located in central Argentina, we analyse in what ways technology is contributing to the accumulation of capital in a context where prevailing strategies resting on farm‐scale extension are no longer effective. We identify two major technological phases that go along with changes in actors' strategies aiming at re‐establishing expanded capital accumulation. These phases allow a better understanding of the mediating role of technology between capital accumulation and the appropriation of nature. In a context of increasing depletion of agro‐ecological conditions, the call for a new wave of innovations can be seen as an attempt to restore that mediating role. As we suggest, this entails broader changes in multiple levels.